ANALISIS PEMAHAMAN MAHASISWA AKUNTANSI DALAM MENGHADAPI MATA KULIAH DASAR-DASAR AKUNTANSI (STUDI PADA MAHASISWA AKUNTANSI-S1 UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU) - Andri Novius (STIE Pelita Nusantara Semarang, 2010)
The aim of this research is to prove empirically about the performance of undergraduate accounting students derive fom SMK accounting majors, SMA Social Majors and MA in conceivingbasic accounting course. Basic accounting course based on the knowledge of Assets, Liabilities, and Equity.Data were collected by using questionnaire. Population and sample is sixties accounting students of UIN Suska Riau whose registered on semester 3, 5 and 7.This research using Statistic tests, that is using Kruskal Wallis test to find out thedifference of knowledge about Assets, Liabilities and Equity on undergraduate accounting students. All hypothesis submitted in this research is rejected.